2022
DOI: 10.3389/fgene.2022.950136
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hub genes and miRNAs in Crohn’s disease by bioinformatics analysis

Abstract: Introduction: Crohn’s disease (CD) is a disease that manifests mainly as chronic inflammation of the gastrointestinal tract, which is still not well understood in terms of its pathogenesis. The aim of this study was to use bioinformatics analysis to identify differentially expressed genes (DEGs) and miRNAs with diagnostic and therapeutic potential in CD.Materials and methods: Three CD datasets (GSE179285, GSE102133, GSE75214) were downloaded from the Gene Expression Omnibus (GEO) database. DEGs between normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The detailed results are listed in Supplementary Table 2 . Summarizing the results of our gene enrichment analysis and those in similar studies, we found that the results of KEGG analysis were similar to those of previously reported articles, i.e., IL-17 and TNF-α were significantly enriched in CD 11 , 34 ; however, in BP analysis, our study found that a variety of humoral immunities, especially microbial-associated humoral immunity, were significantly enriched in CD, which has not been previously reported in the literature.
Figure 3 Functional enrichment analysis of DEGs.
…”
Section: Resultssupporting
confidence: 88%
“…The detailed results are listed in Supplementary Table 2 . Summarizing the results of our gene enrichment analysis and those in similar studies, we found that the results of KEGG analysis were similar to those of previously reported articles, i.e., IL-17 and TNF-α were significantly enriched in CD 11 , 34 ; however, in BP analysis, our study found that a variety of humoral immunities, especially microbial-associated humoral immunity, were significantly enriched in CD, which has not been previously reported in the literature.
Figure 3 Functional enrichment analysis of DEGs.
…”
Section: Resultssupporting
confidence: 88%
“…According to the regulatory network, we found that miR-5698, miR-224-5p, and miR-4709-3p regulate multiple key hub genes identified by using cytoHubba’s MCC algorithm ( 31 , 32 ). These miRNAs are presumed to be the key miRNAs for regulating LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology (GO) analysis of DEGs in Histone-H and Histone-L groups was conducted using clusterProfiler R package (version 4.0.5). 17 GO enrichment analyses contain biological process (BP), cellular component (CC), and molecular function (MF). FDR < 0.05 was considered to determine significant enrichment.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%